2020
DOI: 10.1002/chem.201903877
|View full text |Cite
|
Sign up to set email alerts
|

CN‐Modified Imidazopyridine as a New Electron Accepting Unit of Thermally Activated Delayed Fluorescent Emitters

Abstract: Twoe fficient thermally activated delayed fluorescent (TADF) emitters were developed by utilizing CN-modified imidazopyridine as an acceptoru nit. The CN-modified imidazopyridine acceptorw as combined with either an acridine donoro rap henoxazine donor through ap henyll inker to produce two TADF emitters, Ac-CNImPy and PXZ-CNImPy. The acridine-based Ac-CNImPy emitter exhibited sky-blue emission with aC IE coordinate of (0.18, 0.38), whereast he phenoxazine-donor-based PXZ-CNImPy showed greenish-yellowe mission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The red TADF-OLED doped with oDMAC-DPPZ exhibited a considerably higher EQE (13.4%) than the pDMAC-DPPZ-doped OLED (4.0%). Therefore, it was demonstrated that donor substitution at the ortho (11,12) position of the DPPZ acceptor is preferred to the para (10, 13) substitution in the design of highperformance long-wavelength TADF emitters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The red TADF-OLED doped with oDMAC-DPPZ exhibited a considerably higher EQE (13.4%) than the pDMAC-DPPZ-doped OLED (4.0%). Therefore, it was demonstrated that donor substitution at the ortho (11,12) position of the DPPZ acceptor is preferred to the para (10, 13) substitution in the design of highperformance long-wavelength TADF emitters.…”
Section: Discussionmentioning
confidence: 99%
“…Organic-emitter-based thermally activated delayed fluorescent (TADF)-OLEDs are considered competent alternatives to Ph-OLEDs, as internal quantum efficiencies of up to 100% are achievable in both cases. [7][8][9][10][11][12][13] Compared to precious-metalbased phosphorescent emitters, TADF emitters are inexpensive and allow for greater diversity in their design. Organic materials with a small singlet-triplet energy gap (DE ST ) are capable of converting non-radiative triplet excitons to radiative singlet excitons via a reverse intersystem crossing (RISC) process.…”
Section: Introductionmentioning
confidence: 99%
“…H NMR (500 MHz, CDCl3) δ [ppm] = 9.83 (d, J = 0.7 Hz, 2H), 8.49 (d,J = 7.9 Hz,1H,CHAr),2H,CHAr),8.34 (d,J = 2.0 Hz,1H,CHAr),8.31 (d,J = 7.8Hz,2H,CHAr),2H,CHAr),7.82 (dd,J = 7.9 Hz,1.8 Hz,1H,CHAr),7.78 (t,J = 7.8 Hz,1H,CHAr). FAB-MS m/z (%): 341 (11), 307 (22), 289 (13), 219 (9), 191 (9), 167 (9), 155 (30), 154 (100), 153 (10), 152 (10), 149 (9), 147 (13), 139 (17), 138 (37), 137 (65), 136 (71), 135 (9), 131 (10), 124 (11), 121 (11), 120 (12), 119 (13), 117 (9), 115 (10), 107 (24), 105 (13), 97 (11), 95 (13), 91 (23), 90 (10), 89 (18). This article is protected by copyright.…”
Section: Funding Informationmentioning
confidence: 99%
“…, 291 (13), 290 (5), 289 (30), 288 (5), 287 ( 16), 154 (6), 105 (6), 95 (7), 91 (6). 8), 418 (9), 417 (7), 337 (7), 310 ( 6), 233 (6), 154 (10), 136 (7). This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation